Effects of different n-6/n-3 polyunsaturated fatty acids ratios on lipid metabolism in patients with hyperlipidemia: a randomized controlled clinical trial - Yang, Yiwei; Xia, Yanping; Zhang, Baixi; Li, Dan; Yan, Jiai; Yang, Ju; Sun, Jing; Cao, Hong; Wang, Yingyu; Zhang, Feng (Frontiers in Nutrition, 2023)
Background and aims: Intake of n-3 polyunsaturated fatty acids (PUFA) is helpful for cardiometabolic health. It improves lipid metabolism, and increasing n-3 PUFA is often considered beneficial. However, the role of n-6/n-3 in the regulation of lipid metabolism has been much debated. Therefore, this study was performed on the effect of different proportions of n-6/n-3 diet on lipid metabolism, and quality of life in patients with hyperlipidemia, aiming to explore appropriate proportions of n-6/n-3 to provide the theoretical basis for the development and application of nutritional blended oil in the future. Methods: These 75 participants were randomized and assigned into three groups, which received dietary oil with high n-6/n-3 PUFA ratios (HP group: n-6/n-3 = 7.5/1), dietary oil with middle n-6/n-3 PUFA ratios (MP group: n-6/n-3 = 2.5/1) or low n-6/n-3 PUFA ratios (LP group: n-6/n-3 = 1/2.5). All patients received dietary guidance and health education were monitored for hyperlipidemia. Anthropometric, lipid and blood glucose parameters and quality of life were assessed at baseline and 60 days after intervention. Result: After 60 days, high-density lipoprotein cholesterol (HDL-c) level was increased (p = 0.029) and Total cholesterol (TC) level was decreased (p = 0.003) in the MP group. In the LP group, TC level was decreased (p = 0.001), TG level was decreased (p = 0.001), but HDL-c level was not significantly increased. At the end of intervention, quality of life’ score was improved in both MP and LP groups (p = 0.037). Conclusion: Decreasing the intake of edible oil n-6/n-3 ratio can improve blood lipids and quality of life. This is significant for the prevention of cardiovascular disease (CVD). It is also essential to note that an excessive reduction of the n-6/n-3 ratio does not further improve the blood lipid metabolism. In addition, the application of perilla oil in nutritional blended oil has particular significance.